Kajian Yuridis Permintaan Maaf Pelaku Tindak Pidana dalam Perspektif Restorative Jusctice - Rika Rahmawati; Warfa`u Dina Zahroh; Dian Rosita (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses the important question of whether an apology from the perpetrator of a criminal offense can remove or mitigate the criminal sanctions imposed. Through theoretical studies, this article explores the role of apologies in the context of criminal law, both as a sign of regret and as a factor to be considered in the judicial process. In Indonesia, although apologies are often used as a form of admission of guilt, legal regulations that explicitly regulate their impact on punishment are still limited.This article also compares the legal approach in Indonesia with other countries that adopt the concept of restorative justice, where apologies can play an important role in resolving legal conflicts. The results of the analysis show that although an apology can lighten the sentence, especially in the context of implementing restorative justice, in general, an apology cannot erase the prescribed punishment.